The Impact of Smart Marketing on Achieving Marketing Superiority: An Applied Study in Iraqi Telecommunication Companies - Dalal Jasim Musher AL- Madhee (Journal of Techniques)
This research aimed to know the impact of smart marketing on achieving marketing Superiority for a sample of administrative leaders in Iraqi telecommunication companies, to achieve this objective, a hypothetical model has been formulated consisting of two main variables. The independent variable is represented by smart marketing through three dimensions: (Digital Cooperative Marketing, Human Capital Empowerment, and Social Capital Cooperation) whereas, the dependent variable is marketing superiority that which consists of three dimensions, namely (Customer Value, Satisfaction Customer, and Loyalty Customer). This research adopted the descriptive analytical approach, and a questionnaire as a tool for collecting research data as (150) valid questionnaires, it is analyzed after has been distributed among the administrative leaders in the Iraqi telecommunication companies. In addition to conducting personal interviews to clarify the topic and the paragraphs of the questionnaire. The data were analyzed and the hypothesis was tested by using appropriate statistical tools through the use of a statistical analysis program (SPSS V. 26). The research reached a set of conclusions and the most important one was that the employment of smart marketing in Iraqi telecommunication companies greatly contributed to the influence of marketing Superiority, which means that the dimensions of smart marketing have an impact on achieving marketing Superiority.